RAQAMLI TEXNOLOGIYALAR ASOSIDA ISHLAB CHIQARISH SAMARADORLIGINI OSHIRISH YO‘LLARI - Zarnigor Maxmudova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract (English): This article examines the role and importance of modern digital technologies in improving production efficiency within the context of the digital economy. In particular, the impact of Artificial Intelligence (AI), the Internet of Things (IoT), Big Data technologies, and automation processes on industrial enterprises is analyzed. The study explores opportunities for reducing production costs, increasing labor productivity, and ensuring efficient use of resources. Furthermore, the economic effectiveness of the smart factory model is highlighted based on international experience. Statistical and correlation analysis methods were used to identify the relationship between digital technologies and production efficiency. The results of the study demonstrate that accelerating digital transformation in industrial enterprises is one of the key economic mechanisms for enhancing production efficiency.